Effects of reduced knee-bend on 100 butterfly performance: A case study uising the men`s Asian and Japanese record holder - Ide, T.; Yoshimura, Y.; Kawamoto, K.; Takise, S.; Kawakami, T. (Biomechanics and Medicine in Swimming XI, 2010)
This article analyzed the 30 year old Asian and Japanese record holder of the men`s 100 meter butterfly. In 2002, Kohei Kawamoto`s best time was 53.22 seconds, and he improved his time to 51.00 seconds in 2009. The most significant difference between Kohei in 2002 and 2009 was the focus on a straight leg butterfly kick technique. When comparing his 2005 stroke to his 2009 stroke, we found that the extent of the straightness of his butterfly kick improved from 39% to 55% (of >170 degrees knee-bending). Additionally, this swimmer improved his speed from 2.5m/s to 2.7m/s, and increased his distance per stroke from 1.894m±0.062 to 2.204m±0.131.